PENERAPAN GAME FROGGY JUMPS UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA MATA PELAJARAN IPAS KELAS III SD NEGERI KEMBANG 01 (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The level of learning achievement in Natural and Social Sciences among elementary school students is still low, indicating the need for the implementation of learning innovations that can increase active participation while deepening students' understanding more optimally. One effort that is considered relevant is the use of game-based learning media designed according to the developmental characteristics and learning needs of elementary school students. The following research aims to examine the effect of the use of the Froggy Jumps game on the learning achievement of third-grade students in the subject of Natural and Social Sciences at SD Negeri Kembang 01. The following research applies a quantitative approach through a quasi-experimental design of one group pretest-posttest. The research population includes all third-grade students of SD Negeri Kembang 01. In the following research, sampling uses a saturated sampling technique, so that all members of the population are used as research samples, with a total of 24. Data acquisition in this research was carried out through the administration of learning outcome tests carried out before and after treatment. Data were analyzed using descriptive and inferential statistical approaches that include the Shapiro-Wilk normality test and the Paired Sample t-Test hypothesis test. The findings of this study indicate that the use of the Froggy Jumps game has a significant impact on improving student learning achievement, as evidenced by the disparity in learning outcomes between the pretest and posttest. These findings confirm that educational game-based learning media has the potential to be a strategic alternative for educators in improving the quality of science learning while strengthening the development of interactive learning models in elementary schools.